ORTHOPEDIC SURGERY IN THE AGING POPULATION: CHALLENGES AND FUTURE DIRECTIONS - Quoc Doanh, Tran; Bui Dieu Linh, Ho; Khoi Luan, Tran; Quoc Hung, Vu; Van Binh, Nguyen; Duc Tai, Tran; Thi Hai An, Dang; Van Khue, Doan; My Huyen, Le; Anh Sang, Nguyen (Journal of Health and Aging, 2025)
The rapid aging of the global population has led to a substantial rise in the demand for orthopedic surgery among elderly patients, particularly for hip, knee, and shoulder arthroplasty. However, age-related physiological decline, comorbidities, and frailty increase the risk of complications and present unique clinical challenges. This review aims to summarize current evidence regarding indications, risks, and evolving strategies in orthopedic surgery for patients aged ≥65 years; We conducted a focused narrative review of the literature published between 2015 and 2025 using PubMed, Scopus, and Google Scholar. Search terms included “orthopedic surgery,” “geriatric patients,” “frailty,” “osteoporosis,” “arthroplasty,” “comprehensive geriatric assessment,” and “enhanced recovery after surgery (ERAS)”. Priority was given to original studies, systematic reviews, meta-analyses, and international guidelines relevant to orthogeriatric care; Evidence synthesis indicates that while elderly patients face higher rates of perioperative complications, successful orthopedic surgery can substantially improve functional recovery and quality of life. Key risk factors include osteoporosis, malnutrition, and frailty, which correlate with delayed healing and increased morbidity. Strategies such as prehabilitation, Comprehensive geriatric assessment, and ERAS protocols have demonstrated effectiveness in reducing hospital stays, lowering complication rates, and enhancing postoperative outcomes; Orthopedic surgery in the aging population offers both opportunities and challenges. Optimal outcomes require a multidisciplinary approach, preoperative optimization, and the integration of evidence-based perioperative strategies. Wider adoption of orthogeriatric care models may improve both safety and sustainability of orthopedic interventions in elderly patients.
Keywords: Orthopedic surgery; Elderly patients; Aging population; Comprehensive geriatric assessment; Enhanced recovery after surgery – ERAS